2007
DOI: 10.1080/13697130701342475
|View full text |Cite
|
Sign up to set email alerts
|

Women's needs for CAM information to manage menopausal symptoms

Abstract: Women feel they are not sufficiently informed to make safe decisions regarding CAM treatment options to alleviate menopausal symptoms. Family physicians are a trusted information source and have an important role in providing women with that information. Brochures containing evidence-based information and a list of newsletters or books that include personal accounts, available in physician's offices and during personal consultations at women's health centers, are offered as a possible solution. A website is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Sveinsdottir and Olafsson (2006) found that women had more negative impressions about HT when they received information from friends and family. Armitage et al (2007) however, found that second-hand information, or 'soft' information was readily accepted by the women they studied but the women did place their trust in the expeti advice offered by health care professionals.…”
Section: Patient Participationmentioning
confidence: 99%
See 4 more Smart Citations
“…Sveinsdottir and Olafsson (2006) found that women had more negative impressions about HT when they received information from friends and family. Armitage et al (2007) however, found that second-hand information, or 'soft' information was readily accepted by the women they studied but the women did place their trust in the expeti advice offered by health care professionals.…”
Section: Patient Participationmentioning
confidence: 99%
“…A survey of hospital inpatients found that 75% of the patients wanted more involvement in decision-making for minor illnesses compared to major illnesses, and patients between 45 and 60 years of age wanted more participation in decision-making compared to those who were under 30 years of age (Doherty & Doherty, 2005). For menopausal women, the desire for involvement stems from a need to have their perimenopausal and menopausal experience validated as a normal transition, and to decrease their anxiety regarding the symptoms they experience, thus improving QOL (Armitage et al , 2007). These numbers alert practitioners to the need for patient centeredness that involves shared decision-making to improve health outcomes.…”
Section: Quality Of Lifementioning
confidence: 99%
See 3 more Smart Citations